Preclinical use of a clinically-relevant scAAV9/SUMF1 vector for the treatment of multiple sulfatase deficiency - Maximiliano Presa; Rachel M. Bailey; Somdatta Ray; Lauren Bailey; Saurabh Tata; Tara Murphy; Pierre-Alexandre Piec; Harold Combs; Steven J. Gray; Cathleen Lutz (Communications Medicine)
Abstract Background Multiple Sulfatase Deficiency (MSD) is a rare inherited lysosomal storage disorder characterized by loss of function mutations in the SUMF1 gene that manifests as a severe pediatric neurological disease. There are no available targeted therapies for MSD. Methods We engineered a viral vector (AAV9/SUMF1) to deliver working copies of the SUMF1 gene and tested the vector in Sumf1 knock out mice that generally display a median lifespan of 10 days. Mice were injected as pre-symptomatic neonates via intracerebroventricular administration, or as post-symptomatic juveniles via intrathecal alone or combination intrathecal and intravenous delivery. Cohorts were assessed for survival, behavioral outcomes, and post-mortem for sulfatase activity. Results We show that treatment of neonates extends survival up to 1-year post-injection. Importantly, delivery of SUMF1 through cerebral spinal fluid at 7 days of age alleviates MSD symptoms. The treated mice show wide distribution of the SUMF1 gene, no signs of toxicity or neuropathy, improved vision and cardiac function, and no behavioral deficits. One-year post treatment, tissues show increased sulfatase activity, indicating functional SUMF1. Further, a GLP toxicology study conducted in rats demonstrates favorable overall safety of this approach. Conclusions These preclinical studies highlight the potential of our AAV9/SUMF1 vector, the design of which is directly translatable for clinical use, as a gene replacement therapy for MSD patients.